Thoracic radiotherapy may improve the outcome of extensive stage small cell lung carcinoma patients treated with first-line immunotherapy plus chemotherapy. Issue 10 (29th September 2022) - Wu, Jia-Jun; Huang, Jing-Wen; Hsu, Kuo-Hsuan; Huang, Yen-Hsiang; Chen, Kun-Chieh; Tseng, Jeng-Sen; Yang, Tsung-Ying; Chang, Gee-Chen
Abstract : Objective: Immunotherapy plus etoposide and platinum (EP)-based chemotherapy is the standard of care for patients with extensive stage–small cell lung carcinoma (ES-SCLC). In the era of immunotherapy, the role of thoracic radiotherapy for ES-SCLC remains unclear. Methods: We retrospectively included ES-SCLC patients treated with first-line EP-based chemotherapy plus atezolizumab or durvalumab at Taichung Veterans General Hospital to evaluate the prognostic role and safety of thoracic radiotherapy. Results: A total of 22 patients were included. The median age was 64 years and most of them were male and smokers. Sixteen patients (72.7%) received durvalumab, while the other 6 patients (27.3%) underwent atezolizumab treatment. Among these patients, 11 (50.0%) had a history of thoracic radiotherapy. There was no significant difference in baseline characteristics between patients with and without thoracic radiotherapy. In the overall population, the objective response rate to immunotherapy plus chemotherapy was 73.7%. The progression-free survival and overall survival were 6.0 months (95% CI: 4.0–7.9) and 13.8 months (95% CI: 8.0–19.6), respectively. The overall survival was significantly longer in patients with thoracic radiotherapy (not-reached [NR] [95% CI NR-NR] vs. 9.6 months [95% CI 2.5–16.6]), respectively ( P value by log-rank test <0.001). Both multivariate analysis and subgroup analysis specifically comparing patients with consolidative thoracic radiotherapy and patients with clinical benefits to systemic therapy who did not undergo thoracic radiotherapy indicated that thoracic radiotherapy improved survival. Conclusion: The real-world efficacy of EP-based chemotherapy plus atezolizumab or durvalumab was comparable with that of clinical trials. Thoracic radiotherapy may improve the outcome of ES-SCLC.